EXPERIMENTAL INVESTIGATION OF STROUHAL’S NUMBER LINEARITY FOR DUAL TRAPEZOIDAL BLUFF BODY VORTEX FLOWMETER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, on an experimental facility the signal characteristics of DN50 trapezoidal dual bluff body vortex flow meter are investigated with steady flow. The results are presented for the nine dual trapezoidal bluff body combinations with opening length varying from 40.5mm to 115.5mm with blockage ratio of 0.26, 0.29 and 0.31. For each blockage ratio the influence of three after shape angle (16°, 19° and 22°) are investigated. The vortex frequency is calculated by using zero crossing method. The Linearity of Strouhal's number is used as parameter for comparison. The results show that the vortex frequency increases for the 0.26 and 0.29 blockage ratio by using dual bluff body. For the 0.31 blockage ratio, the vortex frequencies is almost same or less for all after shape angles and opening lengths than the reference single bluff body. The best linearity of Strouhal's number was observed for 22° after shape angle combinations for all blockage ratios.